Impacto da disfunção temporomandibular na qualidade de vida relacionada à saúde bucal de adolescentes - Gabrielle Amaral de Freitas (2020)
The objective of this cross-sectional study was to assess the impact of temporomandibular disorder (TMD) on quality of life related to oral health (HRQoL) among adolescents. Ninety patients undergoing dental treatment at a university clinic in 2019, without previously diagnosed for TMD, aged between 13 and 18 years old, of both sexes, whose guardians consented, participated in the study. The HRQoL was measured by applying the Brazilian version of the Oral Health Impact Profile (OHIP-14) and the diagnosis of TMD was performed using the Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD). Axis I of the instrument was used to assess the presence of Muscle Disorders, Disc Displacement and Joint Disorders, and Axis II measured the presence of Depression, non-specific symptoms including pain and generalized anxiety disorder. In addition, patients were examined clinically for other oral conditions: caries (DMFT), fluorosis (Dean's index), dental trauma (Andreasen & Andreasen), dental esthetic index (DAI) and for the presence of spring-incisor hypomineralization, erosion dental, dental wear facets, geographic and fissured tongue. Their parents / guardians answered socio-economic, demographic and general health questions for adolescents. The data obtained were submitted to descriptive and analytical analysis, with chi-square test, Fisher's Exact, Mann Whitney, and simple and multiple logistic regression models (p <0.05). The prevalence of impact on HRQoL was 34% (95% CI: 24-44), with the domains Psychological discomfort (28%) (95% CI: 18-38), Psychological disability (19%) (95% CI: 10-27) and physical pain (15%) (95% CI: 7-23) more prevalent. TMD was diagnosed in 42% (95% CI: 31-53) of adolescents, and 57.5% (95% CI:) of the patients who reported symptoms were girls. Among Axis I diagnoses, the most prevalent was Joint disorder (40%) (95% CI:), and in Axis II, Depression was the most prevalent disorder (46%) (95% CI: 35-57), followed by non-specific physical symptoms including pain (45%) (95% CI: 34-55) and generalized anxiety disorder (41%) (95% CI: 30-52). In the model adjusted for the variables dental caries, toothache and self-perception of oral health, all diagnoses related to TMD provided by the RDC / TMD, except depression, were associated with the negative impact on HRQoL. The impact on HRQoL was associated with self-report on the adolescent's general and oral health (p = 0.008 and p = 0.011), the presence of TMD (p = 0.033), muscle and joint disorder (p = 0.021 and p = 0.009) and all RDC / TMD Axis II diagnoses (p ≤ 0.005). Among the clinical variables, it was associated with the prevalence of dental caries (p = 0.044) and the report of toothache (p = 0.005). No socioeconomic or demographic variables were associated with HRQoL in bivariate analyzes. The OHIP-14 domain with the highest prevalence, Psychological discomfort, was associated with the following variables: Muscle disorders (p = 0.005), Chronic pain (p = 0.003), Non-specific symptoms including pain (p = 0.039), Generalized anxiety disorder (p = 0.020) and Toothache (p = 0.002). These results show that TMD and its associated diagnoses, general health and clinical factors are involved in the negative impact on HRQoL. After univariate analyzes, those independent variables that presented p ≤ 0.20 were tested for the presence of multicollinearity and, when this was identified among a pair or group of variables, only one of them entered the multiple model, considering the theoretical framework. The fact that the different diagnoses related to TMD obtained by the RDC / TMD have exhibited collinearity with each other, added to the purpose of better understanding the contribution of the various aspects related to TMD in HRQoL, based on the construction of five different multiple models, each of which only one of the possible diagnoses was included as an independent variable of interest. Wald's backward method was used to generate the final models, adjusted odds ratio (OR) values and respective 95% confidence intervals for impact on HRQoL between the categories of independent variables. Adolescents with muscle and / or joint disorders and / or disc displacement were 5 times more likely (95% CI: 1.24–21.3) to have a negative impact on HRQoL (model 1), while for those with chronic pain, nonspecific symptoms including pain and generalized anxiety disorder this chance was 4.7 (95% CI: 1.12–19.44) (model 2), 1.4 (95% CI: 1.12–1.80) ( model 4) and 13 (95% CI: 2.81–60.71) (model 5) times higher in relation to adolescents who did not present these signs and symptoms. Caries experience (DMFT) was another clinical variable that remained associated with the negative impact on HRQoL after adjustment in all models. Further studies with representative samples are necessary to confirm these findings.